Proposta de um sistema de informações sobre os recursos hídricos em Angola - Diogo, Paulo Sérgio dos Santos (2013)
The primary focus of this paper is the proposal of an information system to aid decision making in water resource management in Angola. The role that information systems play in supporting the decision making in the management of water resources has been characterized. A study was conducted on information systems of water resources in Brazil, France and the United States, analyzing the IT infrastructure, the components used and how the information is available, in order to interpret and evaluate the mode of operation as well as their potential for possible adaptation in Angola. From this perspective, a proposal was defined for the conception, implementation, and operation of the system. An initial analysis was then made concerning the development of the information system proposed in terms of the temporal, financial, strategic, human resources, legal and technical points of view. A definition of the proposed design was developed for the implementation and operation of the system. A study of the relationship between the functions (processing, storage, retrieval and dissemination) with the components (database, computing infrastructure, among others) was made. Further, a structure was defined of the water resources information system that can support decision making in water resource management in the country, from the extraction of data through storage in the database, the use of system models in the utilization of a decision support subsystem and a spatial interface, and report generation. The macro structure of the system was outlined along with the organizational structure and task description of each element in the system. The computing infrastructure, from the point of view of architecture, equipment and programs that may be used if the steps for modeling a database are performed and a structured information support system were also determined. From this study, it is concluded that the information system would constitute a technical and organizational milestone, ensuring an integrated management of data on water resources and environmental development of watersheds across the country, gathering information about the water resources through a database that can be queried using tools available on the Internet by any individual. This database must be comprehensive, combining data concerning the quality and quantity of water, as well as information relating to the hydrographic division, cartographic base, administrative division, registry of water users, among others. The information generated by the proposed system will be important for the execution of studies, programs and projects in the recovery and conservation of water resources throughout the country and provide information to support decision-making for proper water management.